1979
DOI: 10.1111/j.1467-6494.1979.tb00206.x
|View full text |Cite
|
Sign up to set email alerts
|

Objective self‐awareness as a nonaversive state: Effect of anticipating discrepancy reduction

Abstract: ABSTRACIThe possibility that self-aware subjects in previous objective sellawareness studies displayed heightened negative affect and avoidance reactions because they were made to focus on pernmnent negative discrepancies was investigated in the present research. Subjects were first induced to regard a negative real-ideal discrepancy as either permanent or reducible in size, and then were either made or not made objectively self-aware. As expected, those self-aware subjects who anticipated no reduction in disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
31
0

Year Published

1981
1981
2013
2013

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(37 citation statements)
references
References 4 publications
(3 reference statements)
6
31
0
Order By: Relevance
“…Franzoi and Brewer (37) argue that individuals low in private self-consciousness engage in selective self-attention, characterized by the tendency to avoid the selfaware state when it is unpleasant or negative. Others have demonstrated that manipulations designed to increase self-awareness are accompanied by a concommitant increase in negative affect (38,39), and that individuals will work to avoid self-awareness (40,41), supporting the contention that self-awareness can be aversive. Conceivably, then, for individuals low on private self-consciousness, forced self-awareness may prove especially aversive given that the natural tendency is to avoid the self-aware state.…”
Section: Discussionmentioning
confidence: 87%
“…Franzoi and Brewer (37) argue that individuals low in private self-consciousness engage in selective self-attention, characterized by the tendency to avoid the selfaware state when it is unpleasant or negative. Others have demonstrated that manipulations designed to increase self-awareness are accompanied by a concommitant increase in negative affect (38,39), and that individuals will work to avoid self-awareness (40,41), supporting the contention that self-awareness can be aversive. Conceivably, then, for individuals low on private self-consciousness, forced self-awareness may prove especially aversive given that the natural tendency is to avoid the self-aware state.…”
Section: Discussionmentioning
confidence: 87%
“…The most plausible interpretation is that self-focused people seek to improve their performance or behavior to enable themselves to feel better. In support of that view, Steenbarger and Aderman (1979) showed that people responded to failure by becoming self-aware and trying to change for the better-but only when there was some prospect of improvement. When there was no chance to improve, people responded to failure by seeking to escape from and avoid self-awareness.…”
Section: Baumeister Et Al / How Emotion Shapes Behavior 179mentioning
confidence: 94%
“…Carver and Seheier; on the other hand, argue that it is only when there is a low probability of successfully reducing a negative discrepancy that selffocus is aversive and that discrepancy-reduction occurs independently of the arousal of affect. (For a detailed discussion of this and other differences between the two formulations, see Carver, 1979, or Carver & Seheier, 1981 Although research generally supports Carver and Seheier's contention that self-focus is avoided only when there is a low probability of successfifl discrepancy reduction (e.g., Carver, Blaney, & Scheiet;Steenbarger & Aderman, 1979), the role of negative affect in motivating discrepancy-reducing behavior is less clear.…”
Section: Self-focused Attentionmentioning
confidence: 93%